First Whole-Genome Sequences of Two Multidrug-Resistant Acinetobacter baumannii Strains Isolated from a Moroccan Hospital Floor - Alouane, Tarek (Genome Announc, 2017)
This report describes the whole-genome shotgun sequences of two multidrug-resistant Acinetobacter baumannii strains, ABE8_07 and ABE12_M, isolated from a Moroccan hospital floor. These two genome sequences will initiate the study and characterization of the Acinetobacter baumannii genome in Morocco.